Thin substrate machining - Ahmad Al Faruqi Ahmad Dahri (2012)
This project focused on the development of cutting process on a thin sheet metal which will then be used as an individual mould. Application devices such as lab-on-a-chip (LOC) make use of this mould to fabricate the device. Micro cutting is one of the fabrication techniques that has been explored and developed to produce such mould. Due to its cheap cost and flexibility in material choices, micro cutting has become the favourable method. However, the challenge was to reduce the burrs that formed in the cutting process. One approach was to make use of angled cutting tools rather than the normal mill cutter. A range of angled cutting tools of 15°, 30°, 40° and 50° were employed for the cutting process. Two types of material were used in the project to make comparisons. Different cutting phase was also done to give variations and thus analyzing the capability of each material under different parameters.